An overview of human handedness in twins - Ooki, Syuichi (Frontiers in Psychology, 2014)
There has been a long-standing debate on the complex correlation between the development of human hand preference and brain lateralization. Handedness, used as a proxy for cerebral lateralization, is a topic of considerable importance because of its potential to reveal the mechanisms of the underlying pathophysiology of problems related to brain development or cognitive systems. Twin studies, which represent an important method of research in human genetics, would provide valuable suggestions to the studies on the relationship between lateralization and cognitive systems. Many studies have been performed using twin subjects; however, the results are inconsistent, partly because of sample size, background assumptions, data limits or inaccuracies, incorrect zygosity classification and/or lack of birth histories. In summary, within the long history and large number of twin studies performed on handedness, a surprisingly large number of controversial findings have been reported, suggesting the complicated nature of this phenotype. In this mini review, the wide variety of twin studies on human handedness performed to date are introduced.